Understanding Limbic-Predominant Age-Related TDP-43 Encephalopathy (LATE): The Intersection of Pathology and Immune Dysregulation - Mansi Singh; Sanjesh Kumar (Proceedings)
Introduction: In the present state, a novel amnesic and AD-like dementia pathology emerges in the ageing brains, namely Limbic-predominant age-related TDP-43 encephalopathy (LATE) [...]